2020
DOI: 10.1186/s13148-020-00855-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation and decreased expression of TMEM240 are potential early-onset biomarkers for colorectal cancer detection, poor prognosis, and early recurrence prediction

Abstract: Background: Gene silencing by aberrant DNA methylation of promoter regions remains the most dominant phenomenon occurring during tumorigenesis. Improving the early diagnosis, prognosis, and recurrence prediction of colorectal cancer using noninvasive aberrant DNA methylation biomarkers has encouraging potential. The aim of this study is to characterize the DNA methylation of the promoter region of TMEM240, as well as gene expression and its effect on cell biological functions and its applications in early dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Low expression of the TMEM240 protein has been observed in about half of patients with inflammatory bowel diseases, which have a three to five times higher risk of developing colorectal cancer. The study’s results showed that hypermethylation and low expression of TMEM240 are potential biomarkers for colorectal cancer detection, poor prognosis, and early recurrence prediction [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low expression of the TMEM240 protein has been observed in about half of patients with inflammatory bowel diseases, which have a three to five times higher risk of developing colorectal cancer. The study’s results showed that hypermethylation and low expression of TMEM240 are potential biomarkers for colorectal cancer detection, poor prognosis, and early recurrence prediction [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, the clinical prediction of prognosis was primarily based on clinicopathological characteristics such as age, pathological grade, and TNM staging. As these clinicopathological characteristics are highly biased, it is difficult to make a precise prediction of the prognosis based on them [ 26 , 27 ]. In recent years, research studies based on the mRNA characteristic (such as alpha-fetoprotein in liver cancer and prostate-specific antigen in prostate cancer, and so on) for predicting the mortality risk of cancer has become a new hotspot for researchers, but so far, none of these studies were able to identify reliable indicators for the prediction of CRC prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the correlation between EHD3 promoter hypermethylation and reduced EHD3 transcript level was significant in both cohorts ( Figure 3 B and Figure 4 A). Because EHD3 promoter hypermethylation was found in 72.6% of Taiwanese CRC tissues, which was higher than SEPT9 hypermethylation found in 60.92% of Taiwanese CRC tissues [ 28 ] and in 44.4% of patients with tubular polyp adenomas, EHD3 hypermethylation can serve as an early indicator of CRC or as a viable auxiliary to the pathological diagnosis of malignant polyps.…”
Section: Discussionmentioning
confidence: 99%